Path model of antenatal stress and depressive symptoms among Chinese primipara in late pregnancy - Li, Yingtao (BMC Pregnancy Childbirth, 2016)
BACKGROUND: Antenatal maternal mental health problems have numerous consequences for the well-being of both mother and child. This study aimed to test and construct a pertinent model of antenatal depressive symptoms within the conceptual framework of a stress process model. METHODS: This study utilized a cross-sectional study design. Inclusion criteria: participants were adult women (18 years or older) having a healthy pregnancy, in their third trimester (the mean weeks gestation was 34.71). Data collection: depressive and anxiety symptoms were measured by Zung’s Self-rating Depressive and Anxiety Scale, stress was measured by Pregnancy-related Pressure Scale, social support and coping strategies were measured by Social Support Rating Scale and Simplified Coping Style Questionnaire, respectively. Analysis: path analysis was applied to examine the hypothesized causal paths between study variables. RESULTS: A total of 292 subjects were enrolled. The final testing model showed good fit, with normed χ(2) = 32.317, p = 0.061, CFI = 0.961, TLI = 0.917, IFI = 0.964, NFI = 0.900, RMSEA = 0.042. This path model supported the proposed model within the theoretical framework of the stress process model. Pregnancy-related stress, financial strain and active coping have both direct and indirect effects on depressive symptoms. Psychological preparedness for delivery, social support and anxiety levels have direct effects on antenatal depressive symptoms. Good preparedness for delivery could reduce depressive symptoms, while higher levels of anxiety could significantly increase depressive symptoms. Additionally, there were indirect effects of miscarriage history, irregular menstruation, partner relationship and passive coping with depressive symptoms. CONCLUSION: The empirical support from this study has enriched theories on the determinants of depressive symptoms among Chinese primipara, and could facilitate the formulation of appropriate interventions for reducing antenatal depressive symptoms, and enhancing the mental health of pregnant women.